Aplikasi Pembelajaran Metode Regresi Logistik Biner Dalam Mengidentifikasi Karakteristik Prokok Aktif Di Provinsi Sumatera Barat Tahun 2020 - Payana, Sandi Dwi; Effendy, Fachriz; Andari, Arnis Wulan; Tarigan, Febry Vista Kristen; Arnita, Arnita (Peneliti.net, 2025)
This study aims to identify the characteristics of active smokers in West Sumatra Province in 2020 using binary logistic regression. The dependent variable in this study is smoking status (active smoker or non-smoker), while the independent variables analyzed include the highest level of education, per capita expenditure, gender, and homeownership. According to data from the Central Bureau of Statistics (BPS), the percentage of the population over 15 years old who smoke in Indonesia in 2020 was 28.69%, with monthly per capita expenditure on cigarettes amounting to 5.99%. This indicates that cigarettes have become a highly favored commodity, even surpassing basic foodstuffs. Additionally, data from the 2018 Basic Health Research (Riskesdas) recorded the prevalence of smoking-related diseases, such as Acute Respiratory Infections (ARI) at 9.3%, heart disease at 1.5%, and hypertension at 34.11%. Despite the health risks of smoking being widely communicated, smoking consumption remains high, while the number of people quitting smoking is relatively low. According to Riskesdas 2018, the proportion of former smokers increased from 4% in 2013 to 5.3% in 2018, while the proportion of non-smokers decreased from 66.6% to 65.9% in the same period. Using binary logistic regression, this study analyzes how the independent variables education level, and per capita expenditure affect an individual's likelihood of being an active smoker. The results indicate that these variables significantly influence the likelihood of an individual being an active smoker. This study provides valuable insights for public health policy in designing more targeted smoking prevention programs, especially in West Sumatra Province, by considering the socio-economic characteristics that influence smoking behavior.